Utilisation-aware VM placement policy for workload consolidation in cloud data centres. (25th August 2022) - Dabhi, Dipak; Thakor, Devendra
In recent years, the demand for cloud services has risen. Data centres must have a growing number of servers to accommodate rising demand for cloud services, and data centres consume a lot of energy. Virtual machine consolidation (VMC) is a strategy for reducing energy consumption in data centres by shutting down underutilised servers while maintaining service levels (SLA). The VMC process is separated into four policies: overloaded host detection, underloaded host detection, virtual machine selection, and virtual machine deployment. The utilisation-aware VM placement (UAVMP) technique is presented in this research work, which efficiently selects the destination host for VMs migrating from overload/underload hosts based on the host's utilisation and resource skewness. The performance is assessed using the CloudSim simulator. When we compare UAVMP results with power-aware best fit decreasing (PABFD), modified best fit decreasing (MBFD), first fit (FF) and least fit (LF), we find that UAVMP outperforms all.